The Effects of Task Based Speaking Instruction on Students’ Speaking Perception as Shambu Secondary School - Dheressa, Moti Alemayehu; Olana, Tamiru; Bekele, Ebisa (JOLLT Journal of Languages and Language Teaching, 2024)
Task-based speaking tasks offer significant benefits to students by providing opportunities to use the target language to convey meaning and engage with real-world topics and tasks. This approach allows students to draw upon their prior knowledge and background experiences to express opinions and ideas effectively. In line with this, the present study aims to investigate the effects of Task-Based Speaking Instruction (TBSI) on the speaking perceptions of students at Shambu Secondary School during speaking skill performances. To achieve this goal, two intact classes were selected from Shambu Secondary School. The treatment group underwent a twelve-week teaching program implementing TBSI, while the comparison group received conventional instruction as per usual practice. Data for this mixed-methods study were collected through speaking perception questionnaires, and both quantitative and qualitative analyses were employed. Quantitative analysis, utilizing ANCOVA, revealed that TBSI positively influenced students' English speaking perception, particularly in areas related to their speaking performances during English language learning. Furthermore, thematic analysis of interview data uncovered several themes highlighting the benefits of TBSI on students' perceptions of their speaking skills performance. In conclusion, the findings of this study have implications for various stakeholders, including educators, policymakers, and curriculum developers. By recognizing the positive impact of TBSI on students' speaking perceptions, educators can consider integrating this approach into their teaching practices to enhance students' language learning experiences. Policymakers and curriculum developers are encouraged to support the implementation of TBSI in language education programs, thereby fostering the development of effective speaking skills among students.